Regulation mechanism of coal gasification in supercritical water for hydrogen production: A ReaxFF-MD simulation. (26th August 2022) - Feng, Huifang; Ren, Yifei; Fan, Chao; Lu, Libo; Wei, Wenwen; Jin, Hui; Guo, Liejin
Abstract: The regulation study on coal gasification process in supercritical water (SCW) can promote the hydrogen production and upgrading of coal utilization. ReaxFF molecular dynamics simulation integration with representative coal model was first introduced to investigate the regulation mechanism of liquid organics on coal gasification in SCW. Hongliulin coal model was constructed and verified its rationality and accuracy. Among the liquid organics, phenols exhibit a positive effect with the H2 number increasing above 34%. The regulation mechanism is dug deeper into from the perspective of the intermolecular interaction and reactive sites. EvdWaals is the main driving force and a maximum of reaction capability of coal molecules reaches 11.01 kJ/mol. The key reaction process in which the hydrogen is greatly improved is the degradation of heavy components under the regulatory effect of phenol. Moreover, the reactive sites of aromatic structure also change from the side chain to conjugated rings. Degradation mechanism of heavy components in the SCWG of coal is summarized. The experimental results verify that H2 yield is increased by 59% and the solid mass is reduced to 0.72 mg with phenol. This conclusion demonstrated the feasibility of the ReaxFF MD simulation method to guide the clean utilization and industrial application of coal gasification in SCW. Highlights: A structural model for Hongliulin bituminous coal was constructed and validated. Regulation method in SCWG of coal was proposed and simulated. Regulation mechanism of hydrogen production was revealed theoretically. Feasibility of the ReaxFF MD method was verified by practical application.